ADRENAL WEIGHT IN THE INDIAN GERBIL. TATERA I. INDICA HARDWICKE. AS RELATED TO BODY-WEIGHT AND REPRODUCTION ACTIVITY - Jain, A (Annals of Arid Zone, 2016)
Indian gerbil. Tatera i. indica Hardwicke, were trapped from Bikaner during 1967-68 at monthly interval. Preserved adrenals were weighed on. a Mettler semi-micro balance. Left adrenal gland of adult male, adult non- pregnant and pregnant gerbil was found to be significantly heavier_ ( PL 0.001") than the right ODe. Highly significant correlations were obtained between adrenal weights and gross body weights among various age classes 01" both the sexes. The monthly adrenal weights in female gerbils were found to be lowest from June to August. a period when the reproductive activity is at its peak. No significant difference, was observed in adrenal weights of pregnant and adult Don-pregnant gerbils. It therefore, appears that reproductive status of female gerbils apparently does not influence adrenal weights. Adrenal weights of the male gerbils having scrotal testes were, 'however, observed to be heavier ( P < O.O1) than those having similar body weights but possessing regressed testes.